Comparative Study Of Free Radical Activity In Plasmodium Falciparum And Plasmodium Vivax Malaria Patients - PRAMOD KAMBLE,; VINOD BHAGWAT,; DHIRAJ J. TRIVEDI,; ANIL BARGALE, (International Journal of Pharma and Bio Sciences, 2011)
The present study was undertaken to study the free radical activity in malaria patients suffering from plasmodium falciparum (n=14) and plasmodium vivax (n=21) against the healthy control subjects (n=25). Lipid peroxidation was assessed by measuring serum lipid peroxide in both groups of malaria patients by using Malondialdehyde as standard. The serum Ceruloplasmin is also studied along with serum Lipid peroxidation. The level of serum Lipid peroxidation was significantly high (p<0.001) in patients with Plasmodium falciparum malaria as compared to Plasmodium vivax infected patients and healthy controls. Increase in serum Lipid peroxidation may be due to over activity of free radical, which corresponds with severity of tissue damage while increase in serum Ceruloplasmin could be due to acute phase response in malaria.